Modification of Cutinase - Kang Zhang (Cutinase: Preparation and Application, 2021)
Based on the crystal structure of T. fusca cutinase (Tfu_0883), 17 amino acid sites that were selected might influence the binding affinity of cutinase to cutin or its ability to recruit the substrate. Among them, 7 mutants exhibited higher hydrolysis activity by using \(ρ\)-nitrophenyl butyrate (\(ρ\)NPB) as substrate, in comparison to that of wild-type. L90A and I213A mutants were discovered to have better hydrolysis ability of tomato cuticle cutin, about 5 and 2.4 times of wild-type, respectively. Molecular dynamics (MD) showed that in L90A, the conformation of the loop 58-64, especially Tyr60 was flipped noticeably towards Ala90, leaving more space for substrate binding. Similarly, the loop 174-182 and F209 in I213A was also found flipped towards the solvent environment, enlarging the substrate binding space, increasing the binding affinity, and eventually facilitating the catalytic process. In addition, T. fusca cutinase that fused with the carbohydrate-binding modules (CBMs) from T. fusca cellulase Cel6A (CBMCel6A) or Cellulomonas fimi cellulase CenA (CBMCenA) also increased binding activity. Fusion enzymes displayed similar catalytic properties and pH stabilities to that of T. fusca cutinase. Its half-life was 53 h at the optimal temperature of 50\(^°\)C. Meanwhile, the adsorption effect of fusion enzymes was also investigated. Results revealed that the adsorption rates of cutinase-CBMCel6A and cutinase-CBMCenA on filter paper reached 63% and 64%, which were 51% and 52% higher than that of native cutinase, respectively, suggesting that better applications in textile bioscouring than native cutinase.